MICROVASCULAR CHANGES AND DIABETIC RETINOPATHY AND NEPHROPATHY PROGRESSION IN CHILDREN AND ADOLESCENTS WITH TYPE 1 DIABETES MELLITUS - Valeria Draganova; Dimitar Dzhelebov; Hristinka Krasimirova Borisova-Zhecheva; Petya Goycheva (Science & Research)

(untitled)
Background: We established that the age at inception of T1DM significantly impacts the long-term risk of developing proliferative retinopathy in affected children and adolescents. Patients with T1DM, diagnosed before the age of 15 are at a significantly higher risk than children diagnosed at age 15 and older. For instance, several studies show changes in microangiopathy the first year of T1DM in children, suggesting that blood sugar changes may easily impact the retinal microvasculature. These changes have a significant impact on lifelong morbidity and mortality. Another target organ can be the kidney. Various studies disclose about thickening of glomerular basement membrane and expansion of the mesangium presented on kidney biopsy in young patients with T1DM. In children with T1DM, alterations in retinal blood vessels play a important role in progression of DR. Essential features of effective treatment plans include strict blood sugar control as well as regular screening to halt disease progression. New strategies offer an optimistic approach to optimizing retinal health and delaying vision loss. To review studies conducted over the last ten years on microvascular changes and diabetic retinopathy and nephropathy in children and adolescents with T1DM. The review will also examine the diagnostic tools used, the results achieved, and the implications for current practice. Methods: This brief literature review was conducted using electronic searches of authorized databases such as PubMed, Medline, and Google Scholar. We searched in the period from 2014 to 2024. We included the articles that focused on T1DM children and adolescents, reported sample sizes, used appropriate methods to measure microvascular changes, and provided sufficient descriptive and analytical data. We then organized the data into subtopics including microvascular changes, diagnostic methods, predisposing factors, and approaches to treating the disease. Results: This work informs us about the association between age of onset of type 1 diabetes and the lifetime risk of diabetic retinopathy and nephropathy, which are serious complications. Conclusion: It is important to detect microvascular changes and start appropriate treatments early in the development of DR in children and young adults with T1DM to prevent progression. Further research and development in this direction will help advance the understanding and treatment of T1DM.